2023
DOI: 10.31020/mutftd.1166386
|View full text |Cite
|
Sign up to set email alerts
|

Dysmenorrhea Problems of Midwifery Students at a University in Terms of Some Related Variables

Abstract: Amaç: Bu çalışma, bir sağlık bilimleri fakültesinin ebelik bölümü öğrencilerinin dismenore sorununu ve etkileyen faktörleri incelemek amacı ile yapıldı. Gereç ve Yöntem: Tanımlayıcı ve ilişki arayıcı tipteki araştırmanın evreni, bir sağlık bilimleri fakültesi ebelik bölümünde öğrenim gören öğrenciden (N=420), örneklemi ise 368 öğrenciden meydana geldi. Veriler; Öğrenci Bilgi Formu (ÖBF) ve Dismenore Etkilenmişlik Ölçeği (DEÖ) ile toplandı. Veriler; yüzdelik dağılım, ortalama, student t testi, tek yönlü ANOVA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Additionally, in another study, it was observed that 93.2% of students followed a low-fat diet, 81.8% engaged in exercise, 41.8% applied abdominal massage, and 34.5% applied heat to the abdomen to alleviate dysmenorrhea symptoms [22]. These findings indicate that young women commonly prefer CAT methods to cope with dysmenorrhea, and these methods play a significant role in overall health practices.…”
Section: Dıscussıonmentioning
confidence: 95%
“…Additionally, in another study, it was observed that 93.2% of students followed a low-fat diet, 81.8% engaged in exercise, 41.8% applied abdominal massage, and 34.5% applied heat to the abdomen to alleviate dysmenorrhea symptoms [22]. These findings indicate that young women commonly prefer CAT methods to cope with dysmenorrhea, and these methods play a significant role in overall health practices.…”
Section: Dıscussıonmentioning
confidence: 95%